2021
DOI: 10.1177/00494755211064657
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for surgical site infection following intramedullary nailing of diaphyseal fractures of the femur and tibia in adult patients at a tertiary hospital in Lusaka, Zambia

Abstract: Our study aimed to identify prognostic factors for surgical site infection following long bone fracture intramedullary nailing at a tertiary hospital in a low-resource setting. This was a longitudinal observational study involving 132 participants enrolled over a one-year period with femoral and tibial diaphyseal fractures scheduled for ORIF. Participant median age was 30 years (range: 26 – 42). The prevalence of surgical site infection was 16%. Male sex (AOR=0.26, 95% CI [0.70–0.98]; p = 0.047) was associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…For example, in certain African societies, gender inequity has been reported to manifest as social and/or structural barriers negatively impacting females [15]. Moreover, recent reports have suggested that, in some African countries, women seek care for their surgical conditions less commonly than men, and those who do undergo surgery experience poorer surgical outcomes [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in certain African societies, gender inequity has been reported to manifest as social and/or structural barriers negatively impacting females [15]. Moreover, recent reports have suggested that, in some African countries, women seek care for their surgical conditions less commonly than men, and those who do undergo surgery experience poorer surgical outcomes [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%